Territorial assertions and the privatization of public space within the Tugu Yogyakarta Heritage District (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Margo Utomo Street in the northern part of the Cosmological Axis of Yogyakarta has transformed into a tourism and local culinary destination. Since food stalls operate within public space, vendors and customers attempt to mark and personalize their movement areas. This phenomenon reflects broader tensions between public accessibility and private appropriation in heritage settings. The study aims to identify the typologies of public space utilization as private workspaces and to analyze their impacts on the comfort quality of spaces. A qualitative method with a case study approach was applied. The Tugu Yogyakarta was chosen due to its historical significance and the complexity of space utilization. Data were analyzed using Altman’s concept of public territory to explore the typologies of privatization and their implication for territoriality and urban inclusivity. The findings reveal two types of territorial claims along Margo Utomo Street made by food vendors and customers. Physical and non-physical elements serve as territorial markers that personalize space. This privatization generates a social gap between paid and unpaid spaces, alters spatial patterns, and shifts the symbolic meaning of the Tugu Yogyakarta. Such dynamics create tensions between its philosophical meaning and everyday practice, posing significant challenges for sustainability. The study highlights the importance of inclusive and participatory approaches to urban planning to safeguard the cultural and spatial integrity of the heritage areas.
Keywords: Heritage area; Inclusive city; Public space privatization; Territorial claim; Tugu Yogyakarta